Stabilization of p21 by mTORC1/4E-BP1 predicts clinical outcome of head and neck cancers - Susana Llanos (Nature Portfolio, 2016)
The molecular pathways involving p21 and mTORC1 are frequently deregulated in head and neck squamous cell carcinomas (HNSCC). Here, Llanos et al. report a mechanism that regulates p21 stability through the mTORC1/4E-BP1 pathway independently of p53, and show that the mechanism is prevalent in HNSCC.